2011
DOI: 10.1016/j.ecresq.2011.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Family income, parent education, and perceived constraints as predictors of observed program quality and parent rated program quality

Abstract: "Family income, parent education, and perceived constraints as predictors of observed program quality and parent rated program quality" (2011). Faculty

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 48 publications
2
17
2
Order By: Relevance
“…Recent research shows that low-income parents have more positive perceptions of the quality of their childcare settings than do higher-income and more educated parents, even if the observed quality is rated more poorly (Torquati et al 2011). Our findings indicate that some of our study participants did have a perception of 'highquality' childcare that aligned with early childhood program standards, but others may have perceived 'high quality' differently and not considered these program standards as essential, or as important as other care characteristics.…”
Section: Parental Preferences For High-quality Carementioning
confidence: 96%
“…Recent research shows that low-income parents have more positive perceptions of the quality of their childcare settings than do higher-income and more educated parents, even if the observed quality is rated more poorly (Torquati et al 2011). Our findings indicate that some of our study participants did have a perception of 'highquality' childcare that aligned with early childhood program standards, but others may have perceived 'high quality' differently and not considered these program standards as essential, or as important as other care characteristics.…”
Section: Parental Preferences For High-quality Carementioning
confidence: 96%
“…Existing evidence from across a number of OECD countries reveals quite varied patterns in child care usage. Higher-income families have access to more regulated forms, and generally better quality ECEC services, while the most disadvantaged segments of the population use lower quality ECEC arrangements (Debacker 2008;Pavolini and Van Lancker 2018;Porter et al 2010;Raikes et al 2005;Torquati et al 2011;Van Lancker and Ghysels 2016). Researchers in British Columbia (BC) (Goelman and Pence 1988) found that level of family resources was highly correlated with the quality of ECEC services parents secure for their children.…”
Section: Introductionmentioning
confidence: 99%
“…The representativeness of these results may be limited, as the respective samples only consider children at specific age groups, and are limited to selected regions. 8 A few other North American studies with similar approaches are summarized in Torquati et al (2011), Howe et al (2013), Bassok et al (2017).…”
Section: Previous Studies and Differences In Information Asymmetriesmentioning
confidence: 99%
“…3 The existing studies often focus on the US market, including an economic study by Mocan (2007) and several studies by education scientists (Cryer and Burchinal 1997;Cryer, Tietze, and Wessels 2002; for an overview see Torquati et al 2011;Bassok et al 2017). These studies focus on differences in the quality ratings of parents and experts.…”
Section: Introductionmentioning
confidence: 99%